"Like Peanut Butter and Jelly": A Qualitative Study of Chiropractic Care and Home Exercise Among Older Adults With Spinal Disability. Issue 11 (22nd July 2022) - Maiers, Michele; Salsbury, Stacie A.
Abstract : Objective: A mixed‐methods, randomized controlled trial comparing short‐ and long‐term chiropractic care and exercise therapy for spinal disability in older adults found no between‐group differences in the primary outcome. However, those who received long‐term management reported greater improvement in neck pain, self‐efficacy, function, and balance. This nested qualitative study explored participants' perceptions of the benefits and drawbacks of chiropractic care and exercise for spine‐related outcomes, with an emphasis on understanding what makes treatment for spine‐related problems worthwhile. Methods: Of 171 individual interviews conducted after completing study treatment, 50 participants (25 per treatment group) were randomly selected for this analysis. Qualitative descriptive analysis included dual coding of verbatim transcripts by 2 investigators (MM and SAS), which was further distilled into a consensus‐derived codebook of themes and organized using NVIVO software. Results: Participants described trial interventions as complementary to one another for spine‐related disability. Chiropractic care was viewed as improving spinal pain and controlling symptoms, while exercise therapy was noted for its long‐term impact on self‐efficacy and self‐management. These older adults considered changes in pain, global sense of improvement, and improved biomechanical function as making treatment worthwhile. Conclusion: Older adults valued nonpharmacologic treatment options that aided them in controlling spine‐related symptoms, while empowering them to maintain clinical benefit gained after a course of chiropractic spinal manipulation and exercise. The complementary nature of provider‐delivered and active care modalities may be an important consideration when developing care plans. This study underscores the importance of understanding participants' values and experiences when interpreting study results and applying them to practice.